An Implementation Project to Expand Access to Teledoulas for Abortion Patients [A52]. (May 2022) - Shapiro, Marit Pearlman; Termulo, Kara; McAllaster, Sara; Raidoo, Shandhini
Abstract : INTRODUCTION: The purpose of this study was to describe the implementation and results of a patient outreach project to offer teledoula services to patients choosing medication abortion in Hawai'i during the COVID-19 pandemic. METHODS: We trained medical student volunteers at John A. Burns School of Medicine (JABSOM) as abortion teledoulas to remotely provide emotional support, education, pain management, and self-advocacy. We offered teledoula services to pregnant patients presenting for medication abortion either in person or via telemedicine appointment at a university-based, outpatient family planning clinic. The teledoulas were notified by the abortion provider when a patient was interested in the service and the assigned teledoula contacted the patient by phone or text message. We conducted initial training and outreach in February 2021 and recorded completed pairings of teledoulas and patients through July 2021. Institutional review board (IRB) committee approval was waived for the study. RESULTS: Of the 15 medical students who attended the teledoula training, 12 (80%) were interested in participating. Of the interested medical students, 100% successfully paired with patients for support. Of the 194 patients who had a medication abortion in the 5 months that this service was offered, 37 (19.1%) were interested in participating in the program and all were contacted by a teledoula via text message. Thirty-three (89%) patients responded to the text message and successfully connected with a teledoula for support during their medication abortion. CONCLUSION: A teledoula service staffed by medical student volunteers can be successfully implemented and provide remote support for patients choosing medication abortion during the COVID-19 pandemic.